Factors Affecting the Capital Market Value of the Lao PDR - Sengphachanh, Saiphone; Siphanthong, Bounthavy; Sengdala, Chansamone (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The purpose of this research is: 1) authenticate the property of the Freedom of the Lao PDR. And 2) the factors that affect the capital market value of the Lao PDR since 201223. The researchers used time series data from the Lao Stock Exchange, the National Statistics Center, and the Central Bank of the Lao PDR, which are quarterly data starting from the first quarter of 2012 to the fourth quarter of 2023, a total of 48 quarters, and used multiple regression analysis with the ordinary least squares (OLS) method to estimate the coefficients of the variables using a statistical program. The results of the research found: the Multi-collinearity problem found that the correlation coefficient of the independent variables with each other is not more than 0.8, indicating that there is no serious Multi-collinearity problem in the model. Also, through checking the autocorrelation problem of the variables, it was found that the statistical value DW = 1.5278 indicates that the expectation of each value of the variable is independent of each other. It means that the factors that the students put into the model of the factors that affect the capital market value of Laos this time are reliable and can be used in the next level of analysis. As for the analysis of the factors affecting the capital market value in Laos, it was found that among the 6 independent variables studied, there is only one variable that is not statistically significant and cannot explain the change in the capital market value. The remaining 5 variables are statistically significant and can explain the change in the capital market value of Laos. In that is the most common factor of the Lao stock exchange (LSX).